Thinking with literature : towards a cognitive criticism - Cave, Terence, 1938- (Oxford University Press, 2016)
To speak of 'thinking with literature' is to make the assumption that literature (in the broadest sense) is neither a side-show nor a side-issue in human cultures: it belongs to the spectrum of imaginative modes that includes both philosophical and scientific thought. Whether one regards it as a practice or as an archive, literature is highly pervasive, robust, enduring, and pregnant with values. Thinking with Literature argues that what it affords above allis a way of thinking, whether for writer, reader, or critic. Literature constitutes one of the prime instruments of cultural improvisation; it is the embodiment of a powerful, inventive, and ever-changing cognitive agency. As such, it invites a cognitive mode of criticism, one which asserts the priority ofthe individual literary work as a unique product of human cognition. In this book, discussions of topics, arguments, and hypotheses from the cognitive sciences, philosophy, and the theory of communication are woven into the fabric of a critical analysis which insists on the value of close reading: a poem by Yeats, a scene from Shakespeare, novels by Mme de Lafayette, Conrad, Frantzen, stories from Winnie-the-Pooh, and many others appear here on their own terms, with their own cognitiveenergies. Written in an accessible style, Thinking with Literature speaks both to mainstream readers of literature and to specialists in cognitive studies.